THE INFLUENCE OF STRENGTH TRAINING IN ACQUIRED IMMUNODEFICIENCY SYNDROME (HIV) INDIVIDUALS (Fiep Bulletin - online, 2014)
Individuals with the Human Immunodeficiency Virus that undergo the Highly Active Antiretroviral Therapy (HAART) commonly present many adverse effects. These side effects reduce their functional capacity due to the loss of muscle mass, metabolic alterations and abnormal body fat distribution. This study examined the question that strength training should be sufficient for the increase in strength, muscle mass and the decrease of body fat in individuals with HIV. Eight physically active men, with HIV and under HAART participated in this study. They underwent a selection based on the Par-Q and Coronary Risk Factor Questionnaires and presented written medical approval prior to the study confirming aptitude for physical activity. All individuals signed a free and clarified written consent. A strength training program with weightlifting machines were studied during a period of 14 weeks. Significant differences were found in levels in standard Leg Press 45 exercises (p
Keywords: HIV; Strength Training